2010
DOI: 10.1111/j.1541-0072.2010.00368.x
|View full text |Cite
|
Sign up to set email alerts
|

Educating Citizens or Defying Federal Authority? A Comparative Study of In-State Tuition for Undocumented Students

Abstract: Recent years have witnessed a proliferation of state government policies addressing immigration‐related issues. This article addresses an example of state policy regarding immigration: since 2001, 11 state legislatures have granted undocumented high school graduates in‐state tuition status should they wish to attend public post‐secondary schools, while 18 others have considered, and rejected, the same policy. We argue that these outcomes are largely explicable by the manner in which the policy is presented and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 20 publications
1
40
0
Order By: Relevance
“…In the case of US citizen college students' developing attitudes, having larger numbers of undocumented immigrants on campus as students is critical to meet the condition of equal status; however most, if not all, undocumented immigrant college students have been prohibited from truly being of ''equal status'' given the number of unique barriers that impact their ability to attend and succeed in college (Muñoz 2015;The UndocuScholars Project 2015). Striving for academic achievement through public education could be seen as sharing a common goal, while having ISRT laws passed might demonstrate that undocumented immigrants have support from authorities within the state (Reich and Barth 2010). One example that illustrates some of these points comes from McLendon et al (2011) who demonstrated how having a larger percentage of foreign-born residents in a state was one factor that influenced progression toward ISRT policies.…”
Section: Intergroup Contactmentioning
confidence: 96%
See 1 more Smart Citation
“…In the case of US citizen college students' developing attitudes, having larger numbers of undocumented immigrants on campus as students is critical to meet the condition of equal status; however most, if not all, undocumented immigrant college students have been prohibited from truly being of ''equal status'' given the number of unique barriers that impact their ability to attend and succeed in college (Muñoz 2015;The UndocuScholars Project 2015). Striving for academic achievement through public education could be seen as sharing a common goal, while having ISRT laws passed might demonstrate that undocumented immigrants have support from authorities within the state (Reich and Barth 2010). One example that illustrates some of these points comes from McLendon et al (2011) who demonstrated how having a larger percentage of foreign-born residents in a state was one factor that influenced progression toward ISRT policies.…”
Section: Intergroup Contactmentioning
confidence: 96%
“…For US citizen students, actual contact with undocumented immigrants may not be possible or known (due to fears of disclosure). In terms of virtual contact, it is possible that in the ISRT states, there may be more positive media content about undocumented peoples given the state's more inclusive stance toward undocumented immigrant educational access or the positive framing toward educating ''kids'' or ''proto-citizens'' needed to pass such legislation in the first place (see Reich and Barth 2010;Reich and Mendoza 2008). For instance, Kim et al (2011) were able to show differences in the ways border and non-border states' news framed the ''illegal'' immigration debate and consequences.…”
Section: Intergroup Contactmentioning
confidence: 99%
“…Research suggests that the policy window surrounding the adoption and enactment of IRT policies was not clear and concise in every state and may reflect a broader time period than the one-year lag I estimate. For some states the adoption of the IRT policy occurred with little fanfare; for others, however, the process was highly contentious and drawn out (Kobach 2007; Reich and Barth 2010; Reich and Mendoza 2008; Russell 2007). In California, for instance, an IRT policy was first passed by the legislature in 2000 but vetoed by the governor.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, case studies on the adoption of IRT policies suggests that the adoption of these policies is largely determined by idiosyncratic political processes related to policy framing (e.g., education vs. immigration), the social construction of the policy targets (e.g., children vs. criminals), and perceptions of jurisdictional authority (state vs. federal; Reich and Barth 2010; Reich and Mendoza 2008). Moreover, examining state legislative agenda setting, a crucial first step to policy adoption, McLendon, Mokher, and Flores (2011) found no evidence that state differences in political ideology, economic influences, or Latino legislative representation contributed to the likelihood that an IRT policy would achieve the legislative agenda.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation